Couple effects of temperature and fatigue, creep-fatigue interaction and thermo-mechanical loading conditions on crack growth rate of nickel-based alloy (Fracture and Structural Integrity, 2022)
The ambient and high-temperature fatigue crack growth behaviors in C(T) and SENT specimens of Ni-based superalloy for turbine disk application were studied in a wide interval of temperatures 25–750°C using a combination a electro- and servohydraulic test systems and fractographic investigations. The fatigue, creep-fatigue interaction and thermo-mechanical in-phase fatigue (TMF IP) crack growth tests are performed under isothermal and dynamic waveforms loading conditions. The interpretation of the experimental results is given in terms of the traditional stress intensity factors and C-integral as well as new normalized cyclic fracture diagrams. It is found that there are definite temperature-sensitive regions separate for harmonic fatigue and creep-fatigue interaction loading conditions in which the crack growth rate of Ni-based alloy increases sharply. Scanning electron microscopy in longitudinal sections containing cracks revealed the mechanisms responsible for fatigue crack initiation and growth. The couple effect of temperature ranging and isothermal and dynamic waveforms loading conditions on fatigue life was discussed.
Keywords: Crack growth rate; Elevated temperature; Fracture resistance parameter; Nickel-based alloy